Comprehensive validation of fasting-based and oral glucose tolerance test–based indices of insulin secretion against gold standard measures. Issue 5 (13th September 2022) - Prystupa, Katsiaryna; Renklint, Rebecka; Chninou, Youssef; Otten, Julia; Fritsche, Louise; Hoerber, Sebastian; Peter, Andreas; Birkenfeld, Andreas L; Fritsche, Andreas; Heni, Martin; Wagner, Robert
Abstract : Introduction: With pre-diabetes and diabetes increasingly recognized as heterogeneous conditions, assessment of beta-cell function is gaining clinical importance to identify disease subphenotypes. Our study aims to comprehensively validate all types of surrogate indices based on oral glucose tolerance test (OGTT) and fasting measurements in comparison with gold standard methods. Research design and methods: The hyperglycemic clamp extended with glucagon-like peptide 1 (GLP-1) infusion and intravenous glucose tolerance test (IVGTT), as well as OGTT, was performed in two well-phenotyped cohorts. The gold standard–derived indices were compared with surrogate insulin secretion markers, derived from fasting state and OGTT, using both Pearson's and Spearman's correlation coefficients. The insulin-based and C-peptide-based indices were analyzed separately in different groups of glucose tolerance and the entire cohorts. Results: The highest correlation coefficients were found for area under curve (AUC) (I0-30 )/AUC (G0-30 ), I30 /G30, first-phase Stumvoll and Kadowaki model. These indices have high correlation coefficients with measures obtained from both insulin and C-peptide levels from IVGTT and hyperglycemic clamp. AUC (I0-120 )/AUC (G0-120 ), BIGTT-AIR0-60-120, I30 /G30, first-phase Stumvoll and AUC (I0-30 )/AUC (G0-30 ) demonstrated the strongest association with incretin-stimulated insulin response. Conclusions: We have identified glucose-stimulated and GLP-1-stimulated insulin secretion indices, derived from OGTT and fasting state, that have the strongest correlation with gold standard measures and could be potentially used in future researches and clinical practice.